2012
DOI: 10.1093/gbe/evs004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Adaptive Benefits of Protein Domain Emergence and Arrangements during Plant Genome Evolution

Abstract: Plant genomes are generally very large, mostly paleopolyploid, and have numerous gene duplicates and complex genomic features such as repeats and transposable elements. Many of these features have been hypothesized to enable plants, which cannot easily escape environmental challenges, to rapidly adapt. Another mechanism, which has recently been well described as a major facilitator of rapid adaptation in bacteria, animals, and fungi but not yet for plants, is modular rearrangement of protein-coding genes. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 114 publications
7
68
0
Order By: Relevance
“…Strikingly, 48% of all P. patens loci are in Physcomitrella-only clusters (Figure 5), which independently supports an analysis based on protein domains where 52% of all P. patens genes have no Pfam domain [80]. Further filtering of these loci including BLASTP against GenPept and EST support indicates that ~22% (7169) of all loci in Physcomitrella-only clusters have no detectable homolog, while at least ~13% (4157) have no homolog but transcript evidence.…”
Section: Resultssupporting
confidence: 73%
“…Strikingly, 48% of all P. patens loci are in Physcomitrella-only clusters (Figure 5), which independently supports an analysis based on protein domains where 52% of all P. patens genes have no Pfam domain [80]. Further filtering of these loci including BLASTP against GenPept and EST support indicates that ~22% (7169) of all loci in Physcomitrella-only clusters have no detectable homolog, while at least ~13% (4157) have no homolog but transcript evidence.…”
Section: Resultssupporting
confidence: 73%
“…In total, 49% (19,365) of all maize genes were assigned to subgenomes 1 or 2 . The remaining 51% likely emerged more recently, e.g., by modular rearrangement of protein encoding domains (Kersting et al, 2012), by the transposition of existing genes (Freeling et al, 2008), or by exon shuffling from helitrons and other transposons leading to fusion genes (Barbaglia et al, 2012). Among the 27,347 genes expressed in this study, 17,402 (64%) genes were assigned to one of the two subgenomes.…”
Section: Discussionmentioning
confidence: 88%
“…The justification for this is that retention rates after gene duplication, which affects the number of paralogs in a protein family, are highly variable between different protein families (Shiu et al 2006; Morel et al 2015). Significant and long deviations from the molecular clock hypothesis, however, are rare at the sequence level (Kumar 2005) and for domain rearrangements (Kersting et al 2012; Moore et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have described changes in domain arrangements (i.e., the N- to C-terminal order of domains in a protein) and concluded that the dominating forces of rearrangement are duplication of protein coding genes, fusion and terminal domain losses (Apic et al 2003; Ye and Godzik 2004; Kummerfeld and Teichmann 2005; Weiner and Bornberg-Bauer 2006; Weiner et al 2006; Wang and Caetano-Anollés 2009; Zmasek and Godzik 2011, 2012; Forslund and Sonnhammer 2012; Moore et al 2013) whereas fissions and emergence of novel domains are rather rare (Kummerfeld and Teichmann 2005; Moore and Bornberg-Bauer 2012; Kersting et al 2012). In all of these studies, domain repeats have been treated as a single domain, i.e., repeat units have been computationally “collapsed” into a single unit for better handling.…”
Section: Introductionmentioning
confidence: 99%